2012
DOI: 10.5213/inj.2012.16.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Course of Oral Prednisolone in Patients with Bladder Pain Syndrome with Fluctuating, Worsening Pain despite Low-Dose Triple Therapy

Abstract: PurposeTriple therapy with gabapentin, amitriptyline, and nonsteroidal antiinflammatory drugs is efficacious for chronic bladder pain syndrome/interstitial cystitis (BPS/IC). However, transient, fluctuating, worsening pain or flare-up symptoms may develop during treatment for a variety of reasons. Here, we assessed the validity of our observational experience regarding a short course of oral prednisolone therapy, which might be of value in the management of flare-up symptoms of BPS/IC.MethodsBetween May 2007 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The importance of this question was highlighted recently in a small longitudinal study of flares, in which some participants reported flares lasting only a few minutes [8] – a shorter duration of flare than had been documented previously in the literature [5, 7, 10] and one that we have since found to be fairly common (30% of female participants reported experiencing minutes-long flares in response to a short survey [9]). This unexpected finding raised the possibility of other lesser-recognized aspects of flares.…”
Section: Introductionmentioning
confidence: 82%
“…The importance of this question was highlighted recently in a small longitudinal study of flares, in which some participants reported flares lasting only a few minutes [8] – a shorter duration of flare than had been documented previously in the literature [5, 7, 10] and one that we have since found to be fairly common (30% of female participants reported experiencing minutes-long flares in response to a short survey [9]). This unexpected finding raised the possibility of other lesser-recognized aspects of flares.…”
Section: Introductionmentioning
confidence: 82%
“…A well-known anti-inflammatory drug, such as prednisolone, is widely used in treating psoriasis, allergic conditions, respiratory disorders and ulcerative colitis. Several studies have shown its effectiveness in improving pain in rheumatoid arthritis, chronic bladder syndrome and athralgia [9][10][11][12][13][14]. However, the administration of a higher dose of prednisolone or administration for a long period may lead to various adverse effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous small, longitudinal study designed to quantify symptom changes during flares, particularly those lasting >1 day , we found unexpectedly that some participants reported flares lasting only a few minutes. As we are not aware of any references to flares of this short duration in the published literature (only flares lasting at least a few hours to several days or weeks have been referenced ), we conducted an exploratory study at two sites of the ongoing Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Epidemiology and Phenotyping study to examine the full range of urological CPPS flares, and to determine which of these flares warrant further study based on their associated healthcare utilization and, more importantly, degree of bother to participants. This type of descriptive information that draws upon patient experiences is critical to inform future studies on flare prevention, treatment and management.…”
Section: Introductionmentioning
confidence: 99%